The auditory and non-auditory brain areas involved in tinnitus. An emergent property of multiple parallel overlapping subnetworks - Vanneste, Sven; De Ridder, Dirk (Frontiers in Systems Neuroscience, 2012)
Tinnitus is the perception of a sound in the absence of an external sound source. It is characterized by sensory components such as the perceived loudness, the lateralization, the tinnitus type (pure tone, noise-like) and associated emotional components, such as distress and mood changes. Source localization of qEEG data demonstrate the involvement of auditory brain areas as well as several non-auditory brain areas such as the anterior cingulate cortex (dorsal and subgenual), auditory cortex (primary and secondary), dorsal lateral prefrontal cortex, insula, supplementary motor area, orbitofrontal cortex (including the inferior frontal gyrus), parahippocampus, posterior cingulate cortex and the precuneus, in different aspects of tinnitus. Explaining these non-auditory brain areas as constituents of separable subnetworks, each reflecting a specific aspect of the tinnitus percept increases the explanatory power of the non-auditory brain areas involvement in tinnitus. Thus the unified percept of tinnitus can be considered an emergent property of multiple parallel dynamically changing and partially overlapping subnetworks, each with a specific spontaneous oscillatory pattern and functional connectivity signature.